International Conference on X-Ray Lasers 2020 2021
DOI: 10.1117/12.2593119
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray microtomography of Zebrafish larvae

Abstract: Hard X-ray micro computed tomography can be used for three-dimensional histological phenotyping of zebrafish embryos down to 1 µm or below without the need for staining or physical slicing. Current advances in zebrafish embryo imaging, however, mostly rely on synchrotron radiation sources or highly advanced laboratory sources, which despite their evident strengths with regard to their beam properties and the implementation of phase contrast imaging techniques, lack accessibility. Therefore, we evaluated the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This study promises a broader understanding of anatomy and corresponding physiology and pathophysiology. Previously, we showed that more than 50 % of anatomical features identified by synchrotron radiation-based micro computed tomography (SRµCT) can also be identified with standard laboratory-based tomography systems [37]. We can, therefore, expect that the cutting-edge laboratory-based systems provide images comparable to the tomography setups at synchrotron radiation facilities.…”
Section: Zebrafish Embryoa Versatile Biomedical Research Modelmentioning
confidence: 99%
“…This study promises a broader understanding of anatomy and corresponding physiology and pathophysiology. Previously, we showed that more than 50 % of anatomical features identified by synchrotron radiation-based micro computed tomography (SRµCT) can also be identified with standard laboratory-based tomography systems [37]. We can, therefore, expect that the cutting-edge laboratory-based systems provide images comparable to the tomography setups at synchrotron radiation facilities.…”
Section: Zebrafish Embryoa Versatile Biomedical Research Modelmentioning
confidence: 99%
“…The use of three-dimensional visualization techniques is crucial in this regard [9][10][11][12][13]. Among these, the X-Ray microtomography (microCT) technique is gaining popularity for researching both healthy embryogenesis and developmental abnormalities [14][15][16]. This is a non-destructive method of visualizing the internal structure of biological objects.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that more than 50% of anatomical features identified by synchrotron radiation-based microcomputed tomography ( ) can also be identified with standard laboratory-based tomography systems. 27 We can, therefore, expect that the cutting-edge laboratory-based systems will provide images comparable to the tomography setups at synchrotron radiation facilities. Such a level of success implies the possibility to easily perform large experimental series of high-resolution imaging fundamental in zebrafish larva-based research activities.…”
Section: Introductionmentioning
confidence: 99%